Efficient Agri-horti farming system for irrigated agro-ecosystem of western plain zone of Uttar Pradesh - Shamim, M; Kashyap, Poonam; Prusty, A K; Verma, Nisha; Jat, P C; Ravisankar, N; Dubey, S K; Panwar, A S (Indian Farming, 2022)
The microclimate of the given crops and their combination reflected the fair to moderate condition. Banana crop was recorded better performing under Poplar+banana based forestry-horti system as compared to the banana sole crop. In another system of Poplarbanana,there was significantly higher concentration of CO2 (596.0 ppm) although the RH (18.2%) and temperature (35.6oC) were lower as compared to banana sole crop. The combination of poplar+turmeric emerged as the most profitable combination as compared to others.